Fatores que interferem na participação das aulas de Educação Física escolar e que promovam a prática de atividade física para além da escola - Boeni, Letícia Fernanda (My University, 2024)
Introduction: Currently, the lack of physical activity has been a major problem in everyday school life. In this sense, this study seeks to discuss the relevance of physical education at school, as well as to affirm the role of working aspects that involve health with students, in order to promote a healthy routine in daily life. Therefore, this work includes the subject of Course Conclusion Work I and II, in the Licentiate Course in Physical Education, at the University of Caxias do Sul, which studies on participation in physical education classes in Elementary School- Final Years . Objectives: The general objective is to verify the factors that interfere in the participation of students in Elementary School - Final Years in Physical Education classes and that promote the practice of physical activity beyond school. Materials and methods: The research is characterized by the qualitative and quantitative method. Data collection was through a questionnaire. Based on the information obtained from the questionnaire, data analysis and the construction of graphs for interpretation and presentation of results were carried out. Results: It was found that the main factors that interfere with the participation of students in Physical Education classes are related to the performance of teachers, highlighting aspects such as the lack of a proposal for diversified classes and innovative content, not only the application of sports as contents. The motivation factor is also important for a good course of classes and student interest during practices. Conclusion: According to the objectives proposed for this research, which were to verify the factors that interfere with student participation in physical education classes, it was found that the reasons that interfere with non-participation are: non- diversification of content, lack of differentiated classes and motivating classes. [resumo fornecido pelo autor]
Introdução: Atualmente a falta da prática de atividades físicas vem sendo um grande problema no cotidiano escolar. Nesse sentido, esse estudo busca discutir a relevância da educação física escolar, bem como, afirmar o papel de trabalhar aspetos que envolvem a saúde com os escolares, a fim de promover uma rotina saudável na vida diária. Diante disso, esse trabalho, contempla a disciplina de Trabalho de Conclusão de Curso I e II, no Curso de Licenciatura em Educação Física, na Universidade de Caxias do Sul, que estuda sobre a participação nas aulas de educação física no Ensino Fundamental- Anos finais. Objetivos: O objetivo geral consiste em verificar os fatores que interferem na participação dos alunos do Ensino Fundamental ? Anos finais nas aulas de Educação Física e que promovem a prática de atividade física para além da escola. Materiais e métodos: A pesquisa é caracterizada pelo método qualitativo e quantitativo. A coleta de dados foi através de um questionário. A partir das informações obtidas pelo questionário, foi feita uma análise dos dados e construção de gráficos para interpretação e apresentação de resultados. Resultados: Verificou-se que os principais fatores que interferem na participação dos alunos nas aulas de Educação Física estão relacionados com a atuação dos professores, evidenciando aspetos como a falta de uma proposta para aulas diversificadas e conteúdos inovadores, não somente a aplicação dos esportes como conteúdo. O fator motivação também é importante para um bom andamento das aulas e interesse dos alunos durante as práticas. Conclusão: De acordo com os objetivos propostos para esta pesquisa, que eram verificar os fatores que interferem na participação dos alunos nas aulas de educação física, constatou-se que as razões que interferem na não participação são: a não diversificação dos conteúdos, falta de aulas diferenciadas e aulas motivadoras. [resumo fornecido pelo autor]
Keywords: Educação física; Ensino fundamental